Evaluation of The Input of The CIPP Stuflebeam Model the Training of Trainer for The National Health Program Indicator Investmen Health - Fitriyanti (Journal Sains and Education, 2023)
The achievements of related unit health programs are less than optimal, due to several factors, one of the supporting resources is human resources, namely trainers. This study aims to describe the input components of the Health Program Trainer Training Program (TPPK) to improve national indicators of health using the CIPP Stuflebeam model. This study used an evaluation research method through a qualitative descriptive approach using the CIPP Stuflebeam model. Methods of data collection using interviews, document study, observation, and questionnaires. The research respondents were structural officials of the Indonesian Ministry of Health's Apparatus Education and Training Center and 44 training participants. The Milles Model and the Interactive Huberman Model were used to analyze the research results. This study found 1. Participants met education and experience criteria, 2. Trainers met qualification & competency standards, 3. Curriculum objectives: clarity of level of knowledge, skills, and attitudes were very good, Appropriateness of material with training objectives, good GBPP, Program Structure: proportion of time adequate theory and practice, Conformity of methods with learning objectives, Training Aids by methods, Evaluation of curriculum relevant to objectives; 4. Available print learning materials are very good: The content and sequence of printed materials are very good, the writing of printed materials is very good, and the physical quality of printed materials is very good while audio-visual learning materials are absent; 5. Good & very good facilities, enough case banks; 6. Funding: APBN. These findings indicate the importance of evaluating the TPPK training program to improve national health indicators after improvements have been made by referring to the recommendations from the research results.